The Impact of SOX on Earnings Quality: Evidence from Italy and United Kingdom - Mäki, Juha (My University, 2011)
The need for reliable financial information and a large number of major accounting and corporate scandals and frauds occurred between years 2000–2002 was a reason to create a United States federal law called Sarbanes-Oxley Act (SOX) year 2002. There are a lot different kind of opinions regarding the cost and benefits of SOX. The purpose of this study is to extend the literature on earnings quality and the influence of SOX in different kind of investor protection environment. There has been a lack of a suitable benchmark in earlier studied mainly made in U.S. The main idea of this study is to compare four groups of different environment with each other: private firms in United Kingdom whose parents are listed in the U.S., private firms in United Kingdom whose parents are listed in United Kingdom, private firms in Italy whose parents are listed in the U.S. and private firms in Italy whose parents are listed in Italy. There are some key issues, when differences of earnings management in EU countries are analyzed. Leading elements are investor protection, legal system, form of enterprise, enforcement mechanisms based on an institutional oversight aimed at controlling and securities regulation concerning regular reporting and Initial Public Offerings (IPOs) prospectus disclosure requirements. The main finding of this study is that the situation concerning the effects of SOX is different in Italy and United Kingdom. First, private firms complying SOX in UK have higher earnings quality than companies whose parents are listed in UK. However the situation is reversed in Italy. There firms complying SOX have lower level of earnings quality than non-compliers.
Keywords: SOX; earnings management; investor protection in Italy and United Kingdom; abnormal accruals; family firms; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|